1995
DOI: 10.1007/bf02053850
|View full text |Cite
|
Sign up to set email alerts
|

Results of rectocele repair

Abstract: Rectocele is one cause of constipation that can be treated with good results. Preoperative use of vaginal digitalization is not mandatory for a good postoperative result. Defecography is an important complement to physical examination. Patients with pathologic transit study might have a less favorable outcome of rectocele repair with respect to constipation. More studies about the significance of paradoxic sphincter reaction in these patients are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
1
21

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(156 citation statements)
references
References 31 publications
11
123
1
21
Order By: Relevance
“…The remaining 4 (22%; Group III) were referred to surgical repair. Our results match findings from other series (12,26) . The two most common forms of biofeedback therapy are anal manometry (used in the present study) and electromyography of the anal sphincter (13) .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The remaining 4 (22%; Group III) were referred to surgical repair. Our results match findings from other series (12,26) . The two most common forms of biofeedback therapy are anal manometry (used in the present study) and electromyography of the anal sphincter (13) .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the technique can not be used to quantify contrast retention. Some authors have suggested that rectocele should not be repaired if the contrast is completely eliminated during defecography (26) . Others have failed to demonstrate any correlation between defecography findings and surgical outcome (14,16) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Although surgery seems to correct anatomical defects, many side effects may occur (in approximately 50% of cases), such as constipation, fecal incontinence, incomplete bowel emptying, and sexual dysfunction. 193 Surgical treatment for internal rectal prolapse is controversial and is only considered when conservative treatments fail to alleviate the patient's symptoms. 194 Abdominal operations include techniques involving suspension of the prolapsed rectum with or without foreign materials, and sigmoid resection with or without rectopexy.…”
Section: 188mentioning
confidence: 99%